Aprotic Lithium‐Carbon Dioxide Batteries: Reaction Mechanism and Catalyst Design. Issue 10 (4th July 2022) - Xu, Yunyun; Xia, Yujiao; Xue, Hairong; Gong, Hao; Chang, Kun; He, Jianping; Wang, Tao; Ma, Renzhi
Abstract: In recent years, the combustion of fossil fuels leads to the release of a large amount of CO2 gas, which induces the greenhouse effect and the energy crisis. To solve these problems, researchers have turned their focus to a novel Li‐CO2 battery (LCB). LCB has received much attention because of its high theoretical energy density and reversible CO2 reduction/evolution process. So far, the emerging LCB still faces many challenges derived from the slow reaction kinetics of discharge products. In this review, the latest status and progress of LCB, especially the influence of the structure design of cathode catalysts on the battery performance, are systematically elaborated. This review summarizes in detail the existing issues and possible solutions of LCB, which is of high research value for further promoting the development of Li‐Air battery. Abstract : The latest research status of Li‐CO2 batteries is introduced from the aspects of working mechanism, type of cathode catalysts and structural optimization design.